Analysis of Sour Porridge Microbiota and Improvement of Cooking Quality via Pure Culture Fermentation Using Lacticaseibacillus paracasei Strain SZ02 - Wang, Cheng; Xu, Yunhe; Yu, Bin; Xiao, Aibo; Su, Yuhong; Guo, Haonan; Zhang, Huajiang; Zhang, Lili (Frontiers in Microbiology, 2021)
Sour porridge is a traditional Chinese food produced by natural fermentation of broomcorn millet (Panicum miliaceum) soaked in an acid solution. However, the composition of the microbiota involved in different stages of this natural fermentation process and the product maturity time are variable, resulting in sub-optimal industrial-scale production. In this study, the microbial composition of sour porridge at different fermentation times was analyzed through high-throughput sequencing, and a pure culture fermentation process was established to optimize production process and improve the edible quality of the porridge. In natural fermentation, Firmicutes and Proteobacteria were abundant throughout the process. Specifically, Aeromonas, Acinetobacter, and Klebsiella were dominant on fermentation days 1-5 (group NF-1, NF-3, NF-5), while Lactobacillus and Acetobacter gradually became the dominant bacteria on fermentation day 7 (group NF-7). The microbial diversity indices Chao, Shannon, and Simpson increased initially but decreased with time, and the indices for group NF-3 were significantly higher than those for the other groups (P < 0.05). Compared to that in group NF-3, the abundance of functional genes and downstream metabolic pathways related to amino acid, lipid, and monosaccharide metabolism was increased in group NF-7. However, the abundance of genes involved in pathways related to starch and sucrose metabolism was significantly reduced. Further, we isolated one strain of acid-producing bacteria from sour porridge, identified as Lactobacillus paracei by 16SrRNA sequencing and annotated as strain SZ02. Pure culture fermentation using this strain significantly increased the relative starch and amylose contents of the porridge, while decreasing the lipid, protein, and ash contents (P < 0.05). The pure culture-fermented also showed improved edible quality and pasting properties, with significantly enhanced water absorption, expansion rate, iodine blue value (IBV) and dry matter of rice soup (DMRS) and peak viscosity, and breakdown but significantly decreased final viscosity and setback (P < 0.05). These findings suggest that sour porridge produced using strain SZ02 has superior edible qualities and this strategy may be exploited for its industrial production.